2017
DOI: 10.1093/gerona/glx239
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antipsychotic Drugs on Long-term Care, Nursing Home Admission, and Death in Dementia Patients

Abstract: BackgroundBehavioral and psychological symptoms of dementia are commonly treated with antipsychotic drugs (APDs), which have been associated with adverse health effects. We examine the effect of APDs on long-term care (LTC), nursing home (NH) admission, and death of dementia patients.MethodsWe used health claims data of the largest German health insurer from 2004 to 2010 and followed newly-diagnosed dementia patients aged 60 years and older into LTC, NH, and until death. Cox proportional hazards models were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
(33 reference statements)
1
12
0
Order By: Relevance
“…People with dementia are often admitted to RACFs because of deteriorating behavioural symptoms, and this factor may contribute to increased psychotropic prescribing during the transition to residential care . Psychotropic therapy may help delay the need for residential care, but may also contribute to medicines‐related harm that increases the risk of admission . These complex relationships require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…People with dementia are often admitted to RACFs because of deteriorating behavioural symptoms, and this factor may contribute to increased psychotropic prescribing during the transition to residential care . Psychotropic therapy may help delay the need for residential care, but may also contribute to medicines‐related harm that increases the risk of admission . These complex relationships require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Several pooled studies and meta-analyses have demonstrated increased risk of cerebrovascular events and mortality with the use of antipsychotics among persons with dementia (11,17,20,21). This was shown in older adults residing nursing homes, which might be due to advanced dementia; hence, higher baseline mortality risk (22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 98%
“…This was accompanied by a decrease in anxiolytics and hypnotics/sedatives, but with an increase in the use of antidepressants from 43.3% in 2000 to 53.8% in 2012 [51]. In comparison, patients in our study used antipsychotics at a lower rate - 6.5% in patients with dementia who died from stroke and registered in Riksstroke compared to 8.1% who died from other causes [52].…”
Section: Discussionmentioning
confidence: 87%